Where the Gaps Lie: Ten Years of Research into Collaboration on BIM-Enabled Construction Projects (Construction Economics and Building, 2017)
A BIM-enabled Construction Project (BIMCP) refers to a project involving relevant BIM tools to generate, exchange and manage project data between project participants. Success in delivering BIMCPs largely relies on how effective project members collaborate. As a result, collaboration on BIMCP has become a growing field of research while a review of studies on collaboration on BIMCPs is still missing. To address this gap, this paper presents the findings of a systematic review on studies devoted to collaboration on BIMCPs over the past 10 years (2006-2016). To this end, 208 studies published in 12 ICT-oriented journals in the construction context are thoroughly reviewed. The findings bring to light that studies on collaboration on BIMCPs are sporadic, isolated and focus on narrowed, limited and disjointed areas associated with collaboration. The study contributes to the field through highlighting the gaps of the existing literature on the topic. This provides a stepping stone to direct future inquiries that target collaboration on BIMCPs.